The ongoing hazard of BB and pellet gun-related injuries in the United States. - McNeill AM; Annest JL; McNeill, A M; Annest, J L (Annals of Emergency Medicine, 1995)
Study Objective: To characterize BB and pellet gun-related injuries treated in US hospital emergency departments.Design: We obtained data through the National Electronic Injury Surveillance System of the US Consumer Product Safety Commission and weighted them to obtain national estimates.Results: We estimate that from June 1, 1992, through May 31, 1993, 32,997 (95% confidence interval [CI], 27,823 to 38,171) people or 12.9 per 100,000 population (95% CI, 10.9 to 14.9) were treated for BB and pellet gun-related injuries. Of this total, 96% (31,547 [95% CI, 26,600 to 36,494]; 12.3 per 100,000 population [95% CI, 10.4 to 14.2]) sustained gunshot wounds. The incidence of BB and pellet gunshot wounds was highest among males (21.0 per 100,000 population [95% CI, 17.7 to 24.3]), children aged 10 through 14 years (71.4 per 100,000 population [95% CI, 57.4 to 85.4]), and blacks (14.6 per 100,000 population [95% CI, 10.3 to 18.9]). Boys aged 10 through 14 years had the highest risk of injury (121.1 per 100,000 population [95% CI, 95.0 to 147.2]). Although most patients (62%) were victims of unintentional shootings, 13.7% were victims of assault. Males aged 10 through 24 years (49.1% of assault cases) had the greatest risk of assault-related BB and pellet gunshot wounds.Conclusion: BB and pellet gunshot injuries continue to represent a substantial public health problem, especially to children and adolescents. Although BB and pellet guns are designed and intended for recreational use and competitive sport, they are sometimes used to inflict harm, most often among teenagers aged 15 through 19 years. Intervention strategies must be developed and implemented to reduce unintentional shootings and assaults associated with BB and pellet guns.